2015
DOI: 10.3109/13880209.2015.1045086
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and antioxidant role of sweetgum (Liquidambar orientalis) oil against carbon tetrachloride-induced hepatotoxicity and oxidative stress in rats

Abstract: It was concluded that SO has a hepatoprotective effect and antioxidant capacity against CCl4 toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…ABTS radical scavenging ability of the sample at different concentrations was determined as described previously with minor modifications [ 17 ]. 7 mM ABTS and 2.45 mM potassium persulfate reacted together in the dark at room temperature for 16 h to produce ABTS radical cation (ABTS+).…”
Section: Methodsmentioning
confidence: 99%
“…ABTS radical scavenging ability of the sample at different concentrations was determined as described previously with minor modifications [ 17 ]. 7 mM ABTS and 2.45 mM potassium persulfate reacted together in the dark at room temperature for 16 h to produce ABTS radical cation (ABTS+).…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the general requirements of phytopharmacology research (Heinrich et al, 2020), we observed type of extract used, the model used, the dose range tested, duration, the minimal active dose, if and what controls were used as shown specifically in Tables 3, 4. In addition, it also has assorted pharmacological effects, e.g., antibacterial (Wang et al, 2010;, insecticidal (Imam, 2013), antidepressant (Min et al, 2018), inhibiting abnormal excitation of uterine smooth muscle (Wang et al, 2014), anti-prostate cancer cells (Atmaca et al, 2020), promoting wound healing (Ocsel et al, 2012) and hepatoprotective (Suzek et al, 2016), which will not be discussed in this article. (Wang et al, 2012b;Gurbuz et al, 2013;Peng et al, 2013) Carvone (Wang et al, 2012b;Peng et al, 2012;Peng et al, 2013) (-)-α-Terpineol Gurbuz et al ( 2013) Terpinen-4-ol (Peng et al, 2012;Gurbuz et al, 2013) Linalool oxide (Furanoid) (Wang et al, 2012b;Gurbuz et al, 2013;Peng et al, 2013) α-Pinene (Wang et al, 2012b;Peng et al, 2012;Gurbuz et al, 2013;Peng et al, 2013;Park 2014) β-pinene (Wang et al, 2012b;Peng et al, 2012;Gurbuz et al, 2013; Huang et al, 2019) Pentacyclic triterpenoids Oleanic acid Wang et al, 2020b;Wang et al, 2020c;Zhang et al, 2020) Oleanonic acid Wang et al, 2020b;Wang et al, 2020c;Zhang et al, 2020) Betulinic acid (Wang et al, 2020b;<...>…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Antibacterial properties [17] and antioxidant activity [24] of the balsam of this tree "Sığla yağı" or "Sığla oil" has been identified with in vitro experiments. Antioxidative activity of Sığla oil in the rat livers, that has been treated with hepatotoxic and oxidative stress, was proofed by Suzek and his colleagues [9]. Results of their experiments were represented the antioxidative and protective effect of Sığla oil on rat livers.…”
Section: New Aspects and Researches For Liquidamdar Orientalismentioning
confidence: 94%
“…Oxidative damage of DNA, proteins and lipids can trigger cardiovascular diseases, cancer and many other problems [8]. Therefore, it is considered that dietary antioxidants may provide protection against oxidative diseases [9].…”
Section: Introduction Phenolic Compoundsmentioning
confidence: 99%